(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: The Alma-Ata Declaration acknowledged the role of traditional herbal medicine for the achievement of ‘Health for All’ and endorsed that proven traditional medicines and health practices should be integrated into the national essential medicine programme for primary health care. Objectives: This study assessed Nigerians’ knowledge on COVID-19, determined their perception on the use of herbal medicine in the treatment of COVID-19, and identified the factors that may influence their choice of acceptance of herbal medicines for the treatment of the disease. Materials and Methods: A descriptive online survey (Google form) method was used to elicit information from 345 consenting adults in Nigeria. 11-point knowledge and 14-point perception scale were used. Data obtained were exported into an Excel sheet and descriptive statistics were used for data analyses. Results: Although there are no globally certified herbal medicines in the treatment of COVID-19, most of the respondents had good knowledge of COVID-19 and good perception about the use of herbal medicine in the treatment of COVID-19 in Nigeria. Majority of the respondents were willing to use herbal medicines if made available for the treatment of COVID-19 and their reasons included its ready availability (70.9%) cost (80.3%) and perceived lack of side effects (63.8%). Conclusion: This study has established the fact that respondents have good basic knowledge of COVID-19. The good perceptions reported in this study towards the use of herbal medicine in the treatment of COVID-19 are indications that herbal medicines, if researched and scientifically proven to be effective in the treatment of the disease, will be most welcome to the Nigerian populace.